(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2018)
Objective: To describe improvement of healing, microbiological changes and presence of biofilm in stage 4 pressure injuries (PI) in patients with spinal cord injury, after the use of polyhexanide. Methods: A “before and after” study realized with five PI patients. Photographic records were collected, microbiological samples of the wound were collected before and after the use of polyhexanide with swab and irrigation-aspiration technique, and biopsy tissue was collected for light microscopy and scanning electron microscopy (SEM) analysis. Results: Wound healing improved. Regarding the microbiological analyses, it was observed a reduction of the number of colonies of Pseudomonas aeruginosa and Staphylococcus aureus and a high number of Acinetobacter baumannii complex after the use of polyhexanide. SEM showed presence of biofilm in the wound in all samples, even after the use of the product. Conclusion: Further studies are necessary to confirm the benefit of the polyhexanide use.